Empirical formula for the dependence of the “optical gap” value on the electron concentration Ne within the range of 10¹⁷cm⁻³ ≤Ne ≤ 10²²cm⁻³ - Fedorovich, О.А. (Вопросы атомной науки и техники, 2013)
The paper presents an empirical formula for the dependence of the “optical gap” value in the nonideal plasma radiation (absorption) spectra on Ne within the electron concentration of 10¹⁷cm⁻³ ≤Ne ≤ 10²²cm⁻³. A comparison of an empirical formula with theoretical formulas previously obtained by other authors is given. It is recommended to apply the empirical formula for determining the electron concentration by the “optical gap” value in the external layers of nonideal plasma to Ne < 10²²cm⁻³. Наводиться емпірична формула залежності величини «оптичної щілини» неідеальної плазми від концентрації електронів у діапазоні 10¹⁷см⁻³ ≤Ne ≤ 10²²см⁻³. Проводиться порівняння емпіричної формули з отриманими раніше теоретичними формулами. Даються рекомендації щодо застосування емпіричної формули для визначення концентрації електронів у зовнішніх шарах неідеальної плазми при Ne < 10²²см⁻³. Приводится эмпирическая формула зависимости величины «оптической щели» неидеальной плазмы от концентрации электронов в диапазоне 10¹⁷см⁻³ ≤Ne ≤ 10²²см⁻³. Проводится сравнение эмпирической формулы с полученными ранее теоретическими формулами. Даются рекомендации по применению эмпирической формулы для определения концентрации электронов в наружных слоях неидеальной плазмы при Ne < 10²²см⁻³.